Networking Strategy of Boards: Correlates, Performance Effects, and Implications for Small and Medium-sized Enterprises - GEORGE, Gerard (Institutional Knowledge at Singapore Management University, 2001)
Development of linkages with the external environment, e.g. interlocks, is a mechanism to access scarce resources. Creating and maintaining these linkages may be an organizational capability that creates a competitive advantage for small and medium-sized enterprises (SMEs). A partial model of networking strategy is proposed, which includes measures of board composition, interlocks, entrepreneurial orientation and environmental hostility. Analysis of 70 community bank Chief Executive Officer (CEO) responses (58% response rate) lends support to the proposition that firms with a networking strategy performed better (higher return on assets (ROA) and higher return on expenditure (ROE)) than those firms that did not actively pursue the development of networks.